Pengaruh Service Quality dan Kepuasan Konsumen terhadap Loyalitas Pelanggan KFC Balikpapan - Armawan, Ivan (Indo-MathEdu Intellectuals Journal, 2023)
Loyalty is a deeply held commitment to purchase or support a preferred product or service again in the future despite situational influences and marketing efforts that have the potential to cause customers to switch. The key to generating high consumer loyalty is delivering high customer value to consumers. The approach used is quantitative research with a type of research (case study) that tests the causal relationship between variables through testing hypotheses that have been formulated. The research population was all KFC customers in Balikpapan using a sampling technique according to the criteria (purposive sampling). The sample for this research consisted of 100 respondents with the criteria of having used KFC products and participated in the KFC program. Hypothesis testing uses a calculation process with a multiple regression analysis approach with the help of the SPSS program. The research results show that service quality has a significant influence on loyalty with a contribution of 59.1%, consumer satisfaction has a significant influence on loyalty with a contribution of 19.6%, and service quality and consumer satisfaction together have a significant influence on loyalty. with a contribution of 60.7%.